Semi-global Interval Observer-Based Robust Control of Linear Time-Invariant Systems Subject to Input Saturation - Zhang, Zhipeng; Shen, Jun; Zhang, Jiyuan; Qiu, Hongling (Circuits, systems, and signal processing, 2024)
This article investigates the issue of robust control based on interval observers for continuous-time linear time-invariant (LTI) systems with input saturation and disturbances. Firstly, an interval observer is derived by resorting to the system’s output information and the interval bounds on the disturbances. Then, a parametric Lyapunov equation (PLE)-based low-gain feedback control method is introduced to guarantee semi-global boundedness. In contrast to the current parametric algebraic Riccati equation (PARE)-based method that requires an iterative approach to solve the PARE online, all relevant parameters in the adopted low-gain design approach are offline determined a priori. Moreover, considering the characteristics of the interval observer, a new stability analysis architecture is given by using a Lyapunov function with a mixture of quadratic and copositive types. Finally, two numerical examples are employed as a means of substantiating the theoretical results.